Pemanfaatan Limbah Cangkang Telur dan Ijuk Daun Aren Sebagai Filter Alami Untuk Penyaringan Polusi Udara - Riska Afriyani; Eva Gusmira (Anggaran : Jurnal Publikasi Ekonomi dan Akuntansi, 2024)
This study investigates the potential use of eggshell waste and sugar palm fibers (ijuk) as natural filters for air pollution. Eggshells, rich in calcium carbonate, and ijuk, with its dense fibrous structure, are hypothesized to effectively capture airborne pollutants. An experimental method was employed to create and test filters made from these materials. Results show that the combination of eggshells and ijuk significantly reduces pollutant particle concentrations, providing an environmentally friendly alternative for air filtration.